2017
DOI: 10.1021/acs.jpca.7b05858
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Reaction Mechanism of Criegee Intermediate CH2OO with Methane and Implications for the Formation of Methanol

Abstract: Criegee intermediates (CIs) play a key role in controlling the atmospheric budget of hydroxyl radical, organic acids, and secondary organic aerosols. In this study, the detailed reaction mechanisms of the simplest Criegee intermediate CHOO and its derivatives with methane (CH) have been systematically investigated theoretically. Two pathways A and B have been identified for the title reaction. In pathway A, CIs can act as an oxygen donor by inserting its terminal oxygen atom into the C-H bond of alkanes, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 68 publications
1
30
0
Order By: Relevance
“…Nowadays, the density functional theory (DFT) method has been widely applied in computational chemistry since its reliability and efficiency in predicting the geometries and properties has been veried by a lot of studies including the CH radical. [30][31][32][33][34][46][47][48][49][50][51][52][53][54][55][56][57] Therefore, all the species in the whole reactions have been fully optimized at the B3LYP/6-311++G** level of theory. Subsequently, vibrational frequency analysis has been performed at the same level of theory to identify the nature of the optimized structures.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, the density functional theory (DFT) method has been widely applied in computational chemistry since its reliability and efficiency in predicting the geometries and properties has been veried by a lot of studies including the CH radical. [30][31][32][33][34][46][47][48][49][50][51][52][53][54][55][56][57] Therefore, all the species in the whole reactions have been fully optimized at the B3LYP/6-311++G** level of theory. Subsequently, vibrational frequency analysis has been performed at the same level of theory to identify the nature of the optimized structures.…”
Section: Methodsmentioning
confidence: 99%
“…All the geometries have been fully optimized at the B3LYP/6-311++G(d,p) level of theory, where the reliability of the method has been verified by numerous systems [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Subsequently, vibrational frequency analysis has been carried out to identify the nature of the optimized species.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In this study, full geometric optimizations were performed employing the B3LYP and M06-2X methods as well as the 6-311++G(3df,3pd) basis set, where the reliability of the DFT method has been confirmed by many systems [ 24 , 25 , 26 , 27 , 28 , 29 ]. As a result, it was found that both methods can give consistent results for the geometry and energy parameters overall.…”
Section: Computational Detailsmentioning
confidence: 99%